Conductive molecularly doped gold films. Issue 48 (29th November 2016) - Naor, Hadas; Divon, Yiftach; Iagher, Lior; Etgar, Lioz; Avnir, David
Abstract : Organic doping of gold films is a new alternative for adsorption, allowing the entrapmernt of a redox couple and affecting the work function. Abstract : We describe a general synthesis of conductive gold thin films doped with entrapped organic molecules, and demonstrate, for the first time, the immobilization of a redox couple within an electrode in a single step. The resulting film is of dual properties: conductivity arising from the gold, and redox behavior originating from the entrapped molecule. Faster electron-transfer rates are found for the entrapped case, compared to adsorption. The conductivity of the film affects the organic molecule–metal interactions, as seen in resistivity measurements, in Raman spectroscopy of the metal-entrapped molecules and from a remarkable red shift of 30 nm in emission spectroscopy. Doping is found to affect the work function of gold. Thin conductive doped metal films are of relevance to a variety of applications such as electrochemical detectors, electrode materials for electrochemical impedance spectroscopy, micro and nano electronics interconnects for packaging and for printed circuit boards. The ability to fine-tune the work function opens the possibility to design the desired energy level gaps for optoelectronic applications such as light emitting diodes (LEDs), solar cells and transistors.